Analisis Studi Kelayakan pada Potensi Bisnis Jamur Crispy ‘MushBoom’ - Izmi Nurshanti, Devia; Jawharul Fadli, Ahmad Zhofaro; Azmi, , Nazhara; Perwito, Perwito (PENG: Jurnal Ekonomi dan Manajemen, 2025)
A business feasibility study is a very important first step in determining the potential and prospects of a business, as well as providing a strong basis for making strategic decisions. This research aims to analyze the business feasibility of MushBoom, a snack food business made from oyster mushrooms, by examining five main aspects: market and marketing, human resources, technical/operational, consumer behavior, and finance. The method used is a qualitative approach through direct observation and interviews with similar business actors, as well as a quantitative approach for financial analysis. The research results show that MushBoom products receive a positive response from consumers, supported by an effective digital marketing strategy. This business can be run with a trained workforce although it requires improved time management. The production process is efficient and uses simple equipment. Purchasing decisions are influenced by product quality, price and packaging. The financial aspect shows that this business has a fast break-even point, with a short payback period and positive NPV. Based on the analysis results, the MushBoom business is feasible to run with recommendations for product diversification, strengthening digital promotions, and increasing human resource training.